(untitled) (Higher Education Politics and Economics, 2016)
The place of athletics in American higher education has been defended and criticized for well over one hundred years (Camp, 1893). Having become such a popular cultural attraction and tradition, as well as a potential method of generating revenue, the role of college athletics has broadened beyond a student-oriented activity. This article reviews the different ways intercollegiate athletics influences the reputation, operation, and quality of higher education.